"EXPERIENCE OF THE EXPECTED?" RACE AND ETHNICITY DIFFERENCES IN THE EFFECTS OF POLICE CONTACT ON YOUTH*. Issue 2 (12th March 2018) - SLOCUM, LEE ANN; WILEY, STEPHANIE ANN
Abstract: Proponents of police reform have called for changes in the way police interact with citizens, particularly with people of color. The rationale, in part, is that when people have more favorable perceptions of their police encounters, they view the police as more just and are more willing to cooperate and comply with the law. To assess whether perceptions of police‐initiated encounters shape law‐related outcomes, we examine how satisfaction with treatment during prior police contact affects procedural injustice, reporting intentions, norms supporting the use of violence, and delinquency. We also explore whether these relationships vary among Blacks, Whites, and Latinos. Our results indicate that youth who have been stopped or arrested fare worse than their counterparts with no police‐initiated contact; however, the potentially negative ramifications of these encounters on all outcomes except violence norms are generally mitigated when youth are satisfied with their treatment. The effects of contact are mostly invariant across racial/ethnic groups when a robust set of control variables are included. We conclude that changing the perceptions of youth regarding how they are treated by the police may mitigate some of the harms of being stopped or arrested, but we caution that these perceptions are shaped by factors aside from police behavior during encounters.